Oxidação Parcial do Metano em catalisadores Rh/Ce-ZrO2 - Oliveira, Raquel Lima (2008)
Hydrogen in the main fuel for fuel cells. The lack of hydrogen infrastructure and the problem of dissolved hydrogen storage had stimulated the development of compact fuel reformers, which are able to produce a rich hydrogen gas mixture from fuels such as the hydrocarbons. Due to its abundance and high ratio H: C, methane (CH4) in an ideal hydrogen source. The process of partial oxidation of the methane is one of the known methods for hydrogen production. In this process the fuel reacts with a limited amount of oxygen to produce hydrogen, purification is required later. The partial oxidation can be applied in different types of hydrocarbons, including heavy fuel and solid hydrocarbons. The present work has investigated the catalytic activity of rhodium supported on γ-Al2O3, CeO2, ZrO2 and Ce-ZrO2, with the purpose to evaluate the influence of the support in the activity of these catalysers in the reaction of partial oxidation of the methane. Al physical-chemistry characterization techniques were used as X ray diffraction (XRD), Difuse reflectance spectroscopy ultraviolet-visible (DRS-UV-vis), temperature programmed reduction (TPR), chemissortion, the model reaction of ciclohexane dehydrogenation and temperature programmed surface reaction (TPSR). TPSR allowed to evaluate the mechanism of CH4 conversion. The analysis of the TPR profiles allowed to conclude that the addition of the metal to the Ce-ZrO2 supports promotes the reduction of the solid solution at lower temperatures than the ones verified in the absence of rhodium. The chemisorption analysis, and the TPSR results, showed that the catalytic activity is related to the amount of metallic sites on the surface. Regarding of the activity test, all the catalysts showed an initial induction time, except for 1.5% Rh/Al2O3. After this induction time, the catalysts kept stable during 24 hours of reaction. In general, it was verified that the catalytic activity increases with the dispersion for all the catalysts.